Paradoks Keaktifan Klasial Studi Komparatif Model Pembelajaran Lintas Situs Dan Fenomena Focus Gap Pada Anak Usia Dini - Maria Yunita Dhema; Putu Arya Oka; Patrisia Serlinda Meo; Maria Edo Meo; Maria Rosamistika Ina Soa; Tekla Dua Ona; Grasiana Sandra Mugi; Edeltrudias Bena; Katarina Ndekung; Maria Wilhelmina Mamo; Maria Fancelina Sugi; Florentina Wonga Rua; Maria Nadila Wea (Arfah BHMS Foundation, 2026)
behavioral indikator defferences between Class A (passive-dependent) and Class B (extrovert-participatory), while identifying the underlying causes of the